KUALITAS PELAYANAN DAN KEPUASAN PEDAGANG DALAM MEMBAYAR RETRIBUSI PASAR - Dita Indah Fitri; Meyzi Hariyanto; Chalid Sahuri (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Service Quality and Trader's Satisfaction In Paying Market Levy. This study aims to determine and analyze the effect of service quality on market merchant satisfaction at Pekanbaru City Market Service in paying market levies. The type of research used is survey research. The population of this study is the market traders and samples of 100 people who carried out accidentally. Technique of collecting data is done by observation, questionnaire and documentation. Data analysis method used is multiple linear regression. The results showed that the dimensions of service quality simultaneously and partially positive and significant effect on market traders satisfaction. The empathy variable is the dominant variable affecting market trader's satisfaction.